Evaluation of Healthy South Texas Asthma Program on improving health outcomes and reducing health disparities among the underserved Hispanic population: using the RE-AIM model - Genny Carrillo; Taehyun Roh; Juha Baek; Betty Chong-Menard; Marcia Ory (BMC, 2021)
Abstract Background In the United States, childhood asthma prevalence is higher among low-income communities and Hispanic populations. Previous studies found that asthma education could improve health and quality of life, especially in vulnerable populations lacking healthcare access. This study aims to describe Healthy South Texas Asthma Program (HSTAP), an evidence-based asthma education and environmental modification program in South Texas, and evaluate its associations with health-related outcomes among Hispanic children with asthma and their families. Methods The RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) planning and evaluation framework was used as an overarching tool to evaluate the impact of the HSTAP. This educational program included 451 children with asthma and their families living in South Texas, an impoverished area at the Texas-Mexico border. The program consisted of (a) the asthma education (2-h) for children with asthma provided by Respiratory Therapy students at the children's schools and (b) the home visit Asthma and Healthy Homes education and walk-through sessions (at baseline and 3 months) for parents and two follow-up visits (6 and 9-12 months later) led by community health workers. The education was provided in either English or Spanish between September 2015 and August 2020 as part of the Healthy South Texas Initiative. A pre-and post-test design was implemented to assess the differences in health outcomes, knowledge, and behaviors using standardized self-reported surveys as reported by parents. Analyses included primary descriptive analyses, generalized estimating equation models, the Wilcoxon signed-rank test, and the McNemar test. Results The HSTAP was significantly associated with improved individual-level outcomes on the frequency of asthma-related respiratory symptoms, including shortness of breath, chest tightness, coughing, and sleep difficulty, among children with asthma, as well as an enhanced asthma knowledge in their family. This study also showed significant associations with children's school attendance and participation in physical activities and family social events and decreased families' worry about their asthma management. Conclusions The RE-AIM model was a helpful framework to assess the HSTAP on all its components. The results suggest that participation in an asthma education and environmental modification program was associated with improved individual-level health conditions and reduced health disparities among children with asthma in low-income communities.